Research trends of acupuncture therapy on postoperative nausea and vomiting from 2011 to 2023: A bibliometric analysis - Qian Li; Qiang Ren; Qin Luo; Xin Yu; Ming Chen; Yuheng Wen; Liuyang Huang; Mingsheng Sun; Shuguang Yu; Sha Yang (Elsevier, 2023)
Background: The utilization of acupuncture as a therapeutic intervention for the management of postoperative nausea and vomiting has experienced a notable increase in its popularity, and the purpose of this analysis is to provide a comprehensive understanding of the level of concern within the academic discipline and the main contributors and their partnership, as well as to identify research focal points and trends. Methods: A comprehensive search was carried out to identify relevant articles on the topic of acupuncture therapy for PONV in the Web of Science and China National Knowledge Internet. The search spanned from January 1, 2011, to June 6, 2023. The annual publications were count to see the degree of scholarly attention devoted to the discipline and how it has changed over time. A statistical analysis of article distribution across various journals was conducted to serve a rough indicator for assessing the quality of articles. And a bibliometric analysis was conducted using the software CiteSpace to visually analyze various aspects of the literature. Analyze authors, institutions and countries to identify the main contributors and their collaborative relationship; and analyze keywords and references to explore research hotspots and trends. Results: This study examined a comprehensive collection of 819 articles focused on acupuncture therapy for PONV, demonstrating a varying upward trend in the quantity of publications. Notably, the most productive author and institution were identified as Zheng Man and Guangzhou University of Traditional Chinese Medicine, respectively. While China had the highest number of publications, the United States held a greater prominence in this specific field. Collaboration among contributors was found to be weak. High-frequency keywords in the publications included ''transcutaneous electrical acupoint stimulation,'' ''electroacupuncture,'' ''pain,'' and so forth. The literature with the highest citation count pertained to "Stimulation of the wrist acupuncture point PC6 for preventing postoperative nausea and vomiting," while the article with the highest centrality was "Consensus Guidelines for the Management of Postoperative Nausea and Vomiting." Several large clusters obtained from the references are also included "postoperative pain," "transcutaneous electrical acupoint stimulation". Nothing pertaining to mechanism study was found in the analysis results. Conclusion: The utilization of acupuncture for the treatment of postoperative nausea and vomiting has been gaining increasing recognition, although there remains room for improvement in the quality of research conducted in this area. Chinese authors and institutions have emerged as significant contributors to this field, while the United States has demonstrated greater proficiency in fostering collaborative efforts. It is imperative to enhance collaboration among these contributors. The current focal points of acupuncture for PONV encompass pain management, electroacupuncture, auricular acupuncture, and transcutaneous electrical acupoint stimulation. Additionally, TEA and enhanced recovery after surgery have been identified as the forefronts of research in this particular domain. In addition, there is still much room for research in the aspect of mechanism and insurance coverage. This study provides an in-depth perspective on acupuncture for PONV, which offers reference material for clinicians with rational choice of therapeutic scheme, educators with hot topics, and researchers with valuable research directions.